Erratum: Anker, A., Hurt, C., Knowlton, N. (2009) “Description of cryptic taxa within the Alpheus bouvieri A. Milne-Edwards, 1878 and A. hebes Kim and Abele, 1988 species complexes (Crustacea: Decapoda: Alpheidae)”. Zootaxa, 2153, 1–23. - Anker, A.; Hurt, C.; Knowlton, N. (Zootaxa, 2012)
(Erratum)